Entre « oubli » et « célébration des exploits » : les représentations militaires des droits humains à l’heure de l’ouverture politique - Lucas Pedretti (Brésil(s))
This article aims to analyze the representations developed within the Armed Forces from the 1970s onwards, to counter the denunciations of human rights violations that began to circulate, first abroad, then within the country. The text presents a sociohistorical analysis, which is empirically supported by documents from the repression services.